Dzieci jako uczestnicy cudownych zdarzeń w "Vita Porphyrii Episcopi Gazensis" Marka Diakona - Milewski, Ireneusz (Vox Patrum, 2006)
The author of this article not only described these miracles, but also made an attempt to interpret them. The first of the miraculous events, employing the ancient motif of a child medium conveying. God’s will to the believers, justifies the claim that the contemporary Christianity adapted pagan divinatio to suit its needs, reshaping it in the Christian mood. The other of the miracles was meant to show the power of both a prayer by a saint man addressed to the only God, and the sign of the cross (the symbol of the new and the only faith), which due to the Porphyry’s prayers, marked the bodies of the children awaiting the rescue. Owing to their being stigmatized with the cross by God’s Providence, they escaped unharmed from the seemingly hopeless situation.